Influence of weather conditions and other factors on the reproductive cycle of Red-breasted Geese Branta ruficollis on the Taymyr Peninsula - Kostin, Igor O; Mooij, Johan H (Wildfowl, 1995)
In the course of research into Red-breasted Goose biology, up to 40 colonies of redbreasts in the Pyasina basin on the Taymyr Peninsula (Russia) were checked every year between 1977 and 1983. One of the aims of the programme was to analyse the influence of annual weather conditions on their population dynamics. It as found that temperature influences the date of arrival in the breeding area, as well as the start of incubation and the main hatching period of the goslings. The percentage of breeding birds and the number of nests per colony (on cliffs) seem to be determined by temperature, precipitation and the snow cover of the cliffs. The percentage of breeders is also influenced by the physiological condition of the birds, which also influences clutch size. Clutch size, together with climatic parameters influence the number of goslings per nest as well as the embryonic and post-embryonic mortality. Reproductive success depends mainly on the physiological condition of adult Red-breasted Geese upon arrival in the breeding area, as well as on the weather of the breeding range during the reproductive period. Success is further influenced by the level of predation by the Arctic Fox and the population and reproductive success of Peregrine Falcons, Rough-legged Buzzards and Herring Gulls.